The method of calculating supercavities - Буйвол, В.М.; Фоміна, Н.Б. (Proceedings of National Aviation University, 2007)
The approximate method of calculation of super cavities form, which allows getting a simple formula for the calculation of form of the cross sections of super cavity for a body that moves in a liquid taking into account the field of gravity and surface tension forces, is considered.